A Roadmap for the Restoration of Mediterranean Macroalgal Forests - Cebrian, Emma; Tamburello, Laura; Verdura, Jana; Guarnieri, Giuseppe; Medrano, Alba; Linares, Cristina; Hereu, Bernat; Garrabou, Joaquim; Cerrano, Carlo; Galobart, Cristina; Fraschetti, Simonetta (Frontiers in Marine Science, 2021)
Canopy-forming macroalgae play a crucial role in coastal primary production and nutrient cycling, providing food, shelter, nurseries and habitat for many vertebrate and invertebrate species. However, in several places, macroalgal forests are in decline and natural recovery is almost impossible when populations become locally extinct. Hence, active restoration emerges as the most profitable strategy to rebuild disappeared forests. In this sense, a significant effort has been dedicated by several EU institutions on the research of new restoring tools for shallow and mesophotic reef habitats (e.g., MERCES EU project and AFRIMED) and, as a result, effective techniques have been proposed to get self-sustaining populations. Recent research points out that macroalgal forest recovery requires a broad spectrum of measures, ranging from mitigating human impacts to restoring the most degraded populations and habitats and that the viability of large restoration actions is compromised by ongoing human pressures (e.g., pollution, overgrazing and climate change). Here a roadmap for macroalgal restoration is proposed to assist researchers and stakeholders in decision-making, considering the most effective methods in terms of cost-effectiveness, including the consideration of background environmental conditions and potential threats. Finally, the challenges currently faced in the restoration of rocky coastal ecosystems under changing climate conditions are also discussed.